The Kazakh future tense forms and translation techniques of rendering them from Kazakh into English (Eurasian Journal of Philology Science and Education, 2021)
The article deals with two relevant problems of language and translation studies. Firstly, it attempts to make a thorough analysis and study of the Kazakh future tense forms as far as there are few materials in English referring to the meaning, usage and formation of the Kazakh future tense forms while the English future tense is thoroughly and well-studied field of language studies and needs no further discussion or clarification. Secondly, the article tries to analyze and determine the translation techniques of rendering future tense forms from Kazakh into English so as to identify and eliminate the problems the translator may come across in the process of translation by applying the principle of comparison. For the principle of comparison makes it possible for us to establish differences and similarities of heterogeneous languages as far as Kazakh and English languages are syntactically, morphologically and structurally different. Lastly, the article may also be of great assistance for those who is learning Kazakh as a secondary language as far as Kazakh is a highly agglutinative language and the grammatical inflections are the principal means used in Kazakh. Moreover, some of the Kazakh future tense forms have a modal meaning and can be quite confusing for foreign language learners. All the examples provided in the last part of the article can be used in teaching translation techniques of grammatical structures in the theory of translation